Physical and mechanical properties of treated kapok fiber reinforced polyester composites - Alsagayar, Zyad Salem (School of Materials Engineering, Universiti Malaysia Perlis, 2010)
The primary objective of this research is to determine the physical and mechanical properties and the characterization of kapok fiber reinforced polyester resin composite of different composition. Several compositions of kapok fiber/polyester composite were prepared in order to study; i- to study the effect of filler loading of treated kapok fiber filled polyester composites. ii- to compare between two different elements chemical treatment on natural fiber (kapok fiber) reinforced polyester composites on mechanical properties. iii- To study the effect of hygrothermal aging on tensile properties of treated kapok fiber reinforced polyester composite.